2011
DOI: 10.1088/0957-4484/22/25/254002
|View full text |Cite
|
Sign up to set email alerts
|

Nanofilamentary resistive switching in binary oxide system; a review on the present status and outlook

Abstract: This review article summarized the recent understanding of resistance switching (RS) behavior in several binary oxide thin film systems. Among the various RS materials and mechanisms, TiO(2) and NiO thin films in unipolar thermo-chemical switching mode are primarily dealt with. To facilitate the discussions, the RS was divided into three parts; electroforming, set and reset steps. After short discussions on the electrochemistry of 'electrolytic' oxide materials, the general and peculiar aspects of these RS sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
445
1
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(461 citation statements)
references
References 130 publications
9
445
1
6
Order By: Relevance
“…2, 3, and 4, it can be reasonably concluded that the rupture and rejuvenation of Cu filament occur at the ZnS/Pt (or ITO) interface. Given that the filament is apt to be ruptured at the weakest position along its length, [1][2][3]51 it very likely has a conical shape, with the base and the tip located at the anodic (AE, Cu) and the cathodic (CE, Pt or ITO) interfaces, respectively. It follows that the filament is most likely to grow from the anode towards the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…2, 3, and 4, it can be reasonably concluded that the rupture and rejuvenation of Cu filament occur at the ZnS/Pt (or ITO) interface. Given that the filament is apt to be ruptured at the weakest position along its length, [1][2][3]51 it very likely has a conical shape, with the base and the tip located at the anodic (AE, Cu) and the cathodic (CE, Pt or ITO) interfaces, respectively. It follows that the filament is most likely to grow from the anode towards the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…At 1000 K, in an x range of 0 0.008 TiO 2 x maintains its rutile, anatase, or brookite phase structure. 22 Outside this x range, the major defects that arise are titanium interstitials (Ti i ) and oxygen vacancies (V O ). [23][24][25][26] Both defect types can explain oxygen-deficient non-stoichiometric TiO 2 x .…”
Section: (C)mentioning
confidence: 99%
“…[1][2][3][4] Unfortunately, sneak current issue, which refers to the undesired current through unselected cells and thus leads to misreading when reading the selected cell, is still a tough obstacle in real application of crossbar RRAMs. 1,5 This issue will be further exacerbate when the selected cell is in the high resistance state (HRS), whereas all unselected cells are in the low resistance state (LRS).…”
Section: Introductionmentioning
confidence: 99%